Effect of Low-Melting-Point Alloys on High-Temperature Hydrolysis Hydrogen Production of Mg-Based Metals - Jianhua Ran; Zhigang Zeng; Zhifu Wang; Shiman Zhang; Lili Ma; Zhonghao Heng (Applied Sciences)
Hydrogen (H2) production from magnesium and its alloys offers an efficient alternative to traditional methods. In magnesium-based hydrolysis, the formation of a Mg(OH)2 passivation layer significantly hinders the reaction, thereby reducing hydrogen production efficiency. To address this issue, increasing the reaction temperature and selecting appropriate materials are essential. This study adjusted the compositions of magnesium alloys (pure Mg, Mg-Al, Mg-Zn) to form low-melting phases (Mg17Al12 and Mg7Zn3). The results demonstrate that as-cast Mg-Al and Mg-Zn alloys exhibit faster reaction rates and lower critical temperatures compared to pure Mg. Specifically, Mg-30wt.% Al and Mg-30wt.% Zn show the fastest reaction rates, with hydrogen purity reaching 99%. Mg-Zn alloys have an induction time of merely 98 s and can achieve complete reaction at 300 °C, while Mg-Al alloys require 174 s and 420 °C. Pure Mg, on the other hand, requires 270 s and 520 °C. Therefore, regarding the critical reaction temperature, the Mg-Zn alloy requires the lowest critical reaction temperature, the Mg-Al alloy requires a moderate reaction temperature, and pure Mg requires the highest critical reaction temperature. In addition, in terms of the performance of hydrogen production through hydrolysis, compared with pure Mg, Mg-30wt.%Al, Mg-20wt.%Zn, and Mg-30wt.%Zn all exhibit good hydrogen production performance through hydrolysis. Their final conversion rates are all higher than that of pure Mg. Among them, Mg-30wt.%Zn has the most excellent hydrogen production performance, followed by Mg-30wt.%Al. The specific conclusions will be analyzed and discussed in detail in the subsequent text.